Brightening and Guiding Single-Photon Emission by Plasmonic Waveguide–Slit Structures on a Metallic Substrate - Guorui Zhang; Jia, Shangtong; Gu, Ying; Jianjun Chen* (Laser & Photonics Reviews, 2019)
Abstract By designing a plasmonic waveguide–slit structure (a nanoslit etched in a silver nanowire) on a silver substrate, an ultrahigh Purcell factor and ultralarge figure of merit (FOM) are numerically predicted. Because of the large field enhancement (>150 times the incident field) and the ultrasmall optical volume (V ≈ 2 × 10−5λ3) of the resonant mode in the metallic nanoslit, the simulations show that the Purcell factor in the system can reach up to FP = 1.68 × 105, which is more than ten times the maximum Purcell factor in previous work (by placing metallic nanoparticles on a metal surface with a nanogap). Because of the utilization of a silver substrate rather than the common dielectric substrate, the mode cutoff of the surface plasmon polariton (SPP) waveguide mode is completely eliminated, which provides a large selection range of the nanowire radii to support the resonant mode in the nanoslit. Moreover, the SPP propagation length is significantly increased by more than 30 times. As a result, an ultralarge FOM of 1.40 × 107 is obtained, which is more than 80 times the maximum FOM in previous work where the metallic nanowire is placed on or surrounded by dielectric materials.
Keywords: bright single-photon emission; efficient guiding; long propagation length; metallic substrates; purcell enhancement